Influence of Inlet Water Flow Rate on Refrigeration System andWater Producing Performance of a New Household Water Purifier - Ma Yiyu; Wu Weidong; Hua Ruoqiu; Wang Li (Zhileng xuebao)
Based on the principle of air humidification-dehumidification, a novel household water purifier with a vapor compression refrigeration system was proposed and established in this study. The influence of the inlet water flow rate on the key parameters of the system performance was analyzed. These performance parameters included the operating conditions of the system, cooling capacity, power consumption, coefficient of performance (COP), water production rate, and water production per unit energy consumption. The results showed that the refrigerant inlet and outlet temperatures of the main components of the system (compressor, evaporator, and auxiliary condenser) and the suction and exhaust pressures of the compressor all showed a downward trend with the increase in the inlet water flow rate under experimental conditions (ambient temperature of 25 °C, circulating air volume of 100 m3/h, inlet water temperature of 25 ℃, inlet water flow rate of 2.5–4.5 L). The system power consumption also showed a downward trend, while the water production per unit energy consumption showed an upward trend. There was an optimal inlet water flow rate of 3.5 L/h when the water production rate, cooling capacity and COP of the system reached their peak values, which were 0.682 L/h, 699 W and 2.44, respectively, and the water production per unit energy consumption was 2.058 L/kWh. The hygienic indicators (i.e., TDS less than 3) and daily production (above 12 L/d) of the purified water in the system can meet the drinking requirements of general households, and the system can also produce domestic hot water not lower than 60 °C, which has wide application prospects.